The modeling and analysis of a power transmission line supplied by a solar power plant - Can, Erol (Array, 2018)
This article deals with the energy transmission line system which feeds from solar energy at the MATLAB Simulink. So, direct voltage is considered to be converted as an alternating voltage by a 35-level inverter after the solar power plant which has the power of 110 MW an produce 360 kV of direct voltage. A line which covers 240 km of distance is preferred to transmit electrical power from the A1 point to an A2 point. Due to this, the required mathematical equations are calculated with a circuit analyzing method for the line modeling in the simulation. Experiments on the model are carried out at the MATLAB Simulink after the creation of an energy transmission line. After that, when measurements are made taking into consideration the A2 node; the capacitor voltage, the transformer current, the A2 node current, and the fault current, values are given according to the converted voltage at the frequencies of 100 Hz, 80 Hz, and 50 Hz. The obtained results demonstrate the success of the proposed line system, while power is distributed with eliminated fault at a long distance at different frequencies.